TIME LAG BETWEEN CATCHING AND CURING OF FISH AND ITS INFLUENCE ON THE FINISHED PRODUCT 1. MACREL - UNNIKRISHNAN NAIR, T S; VALSAN, A P (Fishery Technology, 2025)
A study is made to determine the maximum permissible timelag both under iced and uniced storage conditions between thecatching of mackerel (Rastre!liger k.anagurta) and its curing, so thatthe quality of the finished product is within tolerable limits. Based onphysical, chemical, bacteriological and taste panel studies the maximumtime lag permissible is fixed as 3 brs under unliced conditionand 3 days under iced condition. Icing of fish is also found to affectthe tasting qualities of the finished product.